Program Aplikasi Pengeluaran Dan Penerimaan Kas Berbasis Web Menggunakan Php Pada PT. Gunung Samarinda - Saputra, Efry Ependi; Heldalina; Pebriadi, Muhammad Syahid (P3M Politeknik Negeri Banjarmasin, 2022)
The purpose of this study is to determine the receipt and expenditure information system. The problem in this study is the recording of receipts and disbursement transactions at PT Gunung Samarinda which is still semi-manual using Microsoft Excel and is prone to data input errors. The case study approach used in this study included interviews, documentation, and direct observation. Types of qualitative and quantitative data used in this study. The results of the research are in the form of a cash receipts and disbursement application program that helps PT Gunung Samarinda to make the current system more effective and efficient.